Pathological pathway analysis in an experimental rheumatoid arthritis model and the tissue repair effect of acupuncture at ST36 - Zhang, Yue; Wang, Hui; Gong, Yi-Nan; Yang, Fu-Ming; Wang, Shen-Jun; Liu, Yang-Yang; Gui, Yong-Qing; Xie, Fei; Xu, Zhi-Fang; Guo, Yi (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is an autoimmune disease that generally affects the joints. In the face of inflammation-induced cartilage and bone damage, RA treatment remains insufficient. While research evidence indicates that acupuncture can exert anti-inflammatory and analgesic effects, improve the joint function of RA patients, and delay the disease, data on whether it can promote RA repair is lacking. Findings from the present work demonstrated that both the antigen-induced arthritis (AIA) and collagen-induced arthritis (CIA) models can simulate joint swelling of RA. The AIA model was more stable than the CIA model, with a higher incidence of success arthritis modeling. Moreover, the AIA mice model could simulate the signal molecules and related pathological processes of the autoimmune response in RA, as well as major pathways related to RA and antigen immune response mechanisms. Manual acupuncture (MA) at Zusanli (ST36) significantly improved paw redness and swelling, pain, and inflammatory cell infiltration in the joints in AIA mice. The therapeutic effect of MA on AIA is achieved primarily through the regulation of steroid hormone biosynthesis, cell metabolism, and tissue repair processes. MA at ST36 can increase the gene contents of tissue repair growth factors, including PEG3, GADD45A, GDF5, FGF5, SOX2, and ATP6V1C2 in the inflammatory side joints of AIA mice, as well as the gene expression of anti-inflammatory cytokine IL-10. In conclusion, acupuncture may alleviate RA associated with modulating tissue healing process for joint repair.